Acceptance of Javanese Karawitan in Japan: Appreciation of traditional culture and community activities - Dhanang Respati Puguh; Mahendra Pudji Utama; Rafngi Mufidah (Cogent Arts & Humanities, 2023)
Japanese society has established ways of preserving ancestral traditions and the learning of traditional arts. The gamelan is a traditional musical instrument used in Java and Bali; in Java, gamelan music is also known as karawitan. Karawitan has two classifications: klenengan [purely instrumental music] and gendhing [music and vocal tradition]. Through their efforts to appreciate traditional values, karawitan players can transform their plays through gendhing. This study argues that the dissemination of Javanese karawitan to foreign countries, including Japan, was influenced by the presence of pioneering figures, the existence of communities accommodated to karawitan groups, and activities that popularised this traditional Javanese art to wider audiences and supporting communities. This study used as primary sources karawitan community activities in Japan on Facebook, blogs, and YouTube. The study considers the values germinated by karawitan players in Japan from their motivations. Further, the karawitan community not only places traditional music as a musical practice, but also as a means to contemplate. This study complements existing studies on karawitan in foreign countries by describing how traditional arts entered Japan, and why and how karawitan developed through gamelan ensembles.